ANALISIS DAMPAK PERUBAHAN CURAH HUJAN, LUAS TAMBAK GARAM DAN JUMLAH PETANI GARAM TERHADAP PRODUKSI USAHA GARAM RAKYAT DI KECAMATAN JUWANA KABUPATEN PATI PERIODE 2003-2012 - Yudha Adiraga; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2014)
This research is motivated by the inability of the local salt production to supply the needs of  national salt for consumption and industrial purpose has prompted the government to import salt. As for the problem of this research is "How much influence rainfall, vast salt ponds and the amount of salt peasants against the production of salt in Juwana city". Of the problems that arise, the researchers wanted to analyze the factors that influence the production of salt in Juwana city that is rainfall (X1), extensive salt ponds (X2), and the amount of salt peasants (X3) on the production of salt (Y)In this study using secondary data obtained from the Department of Marine and Fisheries and the BPS Pati. Then performed an analysis of the data obtained in the form of the classical assumption, hypothesis testing by F test and t test analysis and test the coefficient of determination (R2). Techniques of data analysis is multiple regression analysis. The data have been processed produce regression equation as follows :Y = -101.753 X1 + 45.287 X2  + 37.546 X3From the analysis of the partial t test , rainfall significantly and negatively affect the production of salt and the number of farmers positively and significantly affect the production of salt . But the pond though widely variable has a positive effect , has not significantly affect the production of salt . Then through the F test can be seen that the variable rainfall , vast salt ponds , and significant amount of salt peasants together on the production of salt. Adjusted R Square of 0.946 indicates that 94,6 percent of variation in salt production can be explained by the variable rainfall, vast salt ponds, and the amount of salt peasants used in the regression equation. Then the remaining 5,4 percent is explained by other variables outside the three variables used in this study